Composite positive electrode material and preparation method thereof, lithium ion battery and electric equipment
Synchronous synthesis of high-nickel ternary/LLZO composite cathode material through co-precipitation-solid phase method solves the problems of complex preparation process and difficult to control crystal phase composition in the existing technology, achieves efficient performance improvement, simplifies production process and reduces costs.
Patent Information
- Application Number
- CN202510071586.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The preparation process of the existing high-nickel ternary/LLZO composite cathode material is complicated, and the crystal phase composition is difficult to control, resulting in poor performance improvement.
The high-nickel ternary/LLZO composite precursor and positive electrode material were synchronized by co-precipitation-solid phase method. Different complexing agent concentrations and rotation speeds were set through the two co-precipitation processes to obtain the composite positive electrode material precursor, and flux was added during the subsequent solid phase sintering process, so that the LLZO solid electrolyte was tightly coated on the surface of the high-nickel ternary positive electrode material.
The production process of high-nickel ternary/LLZO composite cathode materials is simplified, the production cost is reduced, the lithium ion transmission dynamics is improved, the electrolyte is prevented from contacting directly with the highly active Ni4+, the generation of rock salt phase is reduced, and the phase change reversibility of high-nickel ternary materials is enhanced, and the composite cathode materials with high magnification performance and high cycle stability are obtained.
Smart Images

Figure CN119841359A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a composite positive electrode material and a preparation method thereof, a lithium-ion battery and electrical equipment. Background Art
[0002] The positive electrode material is the key to the comprehensive performance of lithium-ion batteries. High-nickel ternary positive electrode materials have the advantages of high operating voltage and high discharge capacity. However, during the de-lithiation process, high-nickel materials will produce Ni with strong oxidizing properties. 4+ , which is prone to side reactions with the electrolyte, affecting the structural stability of the positive electrode material, thereby reducing the battery cycle life and safety performance.
[0003] Garnet oxide LLZO (Li 7 La 3 Zr 2 O 12 ) has the advantages of wide electrochemical window (>5V), good chemical and thermal stability, and the lithium ion conductivity can reach 10 at room temperature. -4 S cm -1 , is a solid electrolyte material with great development potential.
[0004] Studies have shown that by co-firing the fast ion conductor LLZO with high-nickel positive electrode active materials, LLZO can be evenly coated on the surface of the high-nickel positive electrode active materials, which can effectively inhibit the interfacial side reactions between the high-nickel positive electrode materials and the electrolyte, thereby achieving the purpose of improving the battery's rate performance and cycle life.
[0005] However, the current synthesis of high-nickel ternary / LLZO composite positive electrode materials requires the separate synthesis of positive electrode materials and solid electrolytes, and then co-firing the two to form a composite. The process is cumbersome and complicated, and because the crystal phase formation temperatures of the two are quite different, the crystal phase composition of the composite positive electrode material is difficult to control, resulting in poor performance improvement. Summary of the invention
[0006] The purpose of this application is to provide a composite positive electrode material and a preparation method thereof, a lithium-ion battery and electrical equipment, aiming to solve the problems of complex preparation process and difficult control of crystal phase composition of existing high-nickel ternary / LLZO composite positive electrode materials.
[0007] To achieve the above objectives, the present application provides a method for preparing a composite positive electrode material, comprising: A first mixed salt solution containing nickel, cobalt and manganese, a first complexing agent and an alkali solution are introduced into the bottom liquid of the reaction kettle to perform a first coprecipitation reaction; After the first coprecipitation reaction, a second mixed salt solution containing lanthanum and zirconium, a second complexing agent and an alkali solution are introduced to carry out a second coprecipitation reaction to obtain a precursor slurry; Collecting the precipitate from the precursor slurry, washing, and drying, to obtain a high-nickel ternary / LLZO composite precursor; The high-nickel ternary / LLZO composite precursor is mixed with a lithium source and calcined to obtain a high-nickel ternary / LLZO composite positive electrode material.
[0008] In some embodiments, at least one of the following conditions is met: A. the total metal ion concentration in the first mixed salt solution is 1.4-2.0 mol / L, and the total metal ion concentration in the second mixed salt solution is the same as that in the first mixed salt solution; B. The total mass of the second mixed salt solution introduced is 0.5%-5% of the mass of the first mixed salt solution; C. The first complexing agent and the second complexing agent are aqueous ammonia solutions, the concentration of the first complexing agent is 0.5-2 mol / L, and the concentration of the second complexing agent is 0.2-0.8 mol / L; D. the alkali solution is a NaOH solution, and the concentration of the NaOH solution is 1-4 mol / L; E. The bottom liquid of the reactor is an ammonia solution with a concentration of 9-11 g / L.
[0009] In some embodiments, at least one of the following conditions is met: A. the pH value of the first coprecipitation reaction is 9-12; B. the rotation speed of the first coprecipitation reaction is 400-900 rpm; C. the temperature of the first coprecipitation reaction is 50-60°C; D. the first coprecipitation reaction time is 8-12 h; E. the rotation speed of the second coprecipitation reaction is 700-1200 rpm; F. the pH value and reaction temperature of the second coprecipitation reaction are the same as those of the first coprecipitation reaction; G. both the first coprecipitation reaction and the second coprecipitation reaction are carried out under a protective atmosphere; H. The flow ratio of the mixed salt solution, complexing agent solution and alkaline solution in the two stages is the same; Optionally, the flow ratio of the mixed salt solution, the complexing agent solution and the alkaline solution is 1:0.3:(0.5-2).
[0010] In some embodiments, the step of mixing and calcining the high nickel ternary / LLZO composite precursor with a lithium source comprises: The high-nickel ternary / LLZO composite precursor is mixed with a lithium source and a flux, and then calcined.
[0011] In some embodiments, at least one of the following conditions is met: A. The flux includes LiF, Li 3 PO 4 、LiBiO 3 One or more of; B. The amount of the flux added is 1%-5% of the molar number of the high nickel ternary / LLZO composite precursor; C. The lithium source is one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium sulfate, lithium acetate, lithium phosphate and lithium oxalate.
[0012] In some embodiments, the calcination is divided into two stages. The first stage is to heat to 400-600°C and keep warm for 6-10 hours. The second stage is to heat to 700-1000°C and keep warm for 10 hours. The heating rate is 1-10°C / min. The whole calcination process is carried out in an oxygen atmosphere.
[0013] In some embodiments, the chemical formula of the high nickel ternary / LLZO composite precursor is: Ni a Co b Mn 1-a-b (OH) 2 ·cLa 3 Zr 2 (OH) 17 The chemical formula of the high nickel ternary / LLZO composite positive electrode material is: LiNi a Co b Mn 1-a-b O 2 ·cLi 7 La 3 Zr 2 O 12 , where a≥0.6, 0.1≤b≤0.3, 0.5wt% <c<5wt%。
[0014] The present application also provides a composite positive electrode material, which is prepared by the above-mentioned method for preparing the composite positive electrode material.
[0015] The present application also provides a lithium-ion battery, comprising the above-mentioned composite positive electrode material.
[0016] The present application also provides an electrical device, comprising the above-mentioned lithium-ion battery.
[0017] Compared with the prior art, the beneficial effects of this application include: The preparation method of the composite positive electrode material provided in the present application simultaneously synthesizes the high-nickel ternary / LLZO composite precursor and the positive electrode material. Compared with the traditional composite positive electrode material, which needs to synthesize the high-nickel ternary and LLZO separately and then combine the two through other experiments, the method of the present application is similar to the current ternary positive electrode material synthesis route, which greatly simplifies the production process of the high-nickel ternary / LLZO composite positive electrode material and reduces the production cost. The method of the present application is based on coprecipitation-solid phase reaction. By setting different complexing agent concentrations and rotation speeds in the two-stage coprecipitation process, a composite positive electrode material precursor is obtained, and then in the subsequent solid phase sintering process, a flux is added to make the LLZO solid electrolyte tightly coated on the surface of the high-nickel ternary positive electrode material.
[0018] The synchronously synthesized high-nickel ternary / LLZO composite positive electrode material provided in the present application has a closer contact and more uniform coating between the LLZO solid electrolyte and the high-nickel ternary material, which improves the lithium ion transmission kinetics while preventing the electrolyte from contacting the highly active Ni 4+ Direct contact reduces the production of rock salt phase, and the garnet-type LLZO electrolyte can also enhance the phase change reversibility of high-nickel ternary materials through lithium supplementation strategy, thereby obtaining a composite positive electrode material with high rate performance and high cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0020] Figure 1 A schematic diagram of a process for preparing a composite positive electrode material of the present application; Figure 2 A schematic diagram of the operation flow of a specific embodiment of the method for preparing the composite positive electrode material of the present application; Figure 3 LiNi prepared in Example 1 0.8 Co 0.1 Mn 0.1 O 2 ·SEM image of 2 wt.% LLZO composite cathode material; Figure 4 LiNi prepared in Examples 1 and 2 0.8 Co 0.1 Mn 0.1 O 2 ·2 wt.% LLZO composite cathode material and LiNi prepared in Comparative Example 1 0.8 Co 0.1 Mn 0.1 O 2 XRD pattern of Figure 5 LiNi prepared in Example 1 0.8 Co 0.1 Mn 0.1 O 2 TEM image of 2 wt.% LLZO composite cathode material; Figure 6 The rate performance diagram of the positive electrode materials prepared in Examples 1, 2, 3 and Comparative Example 1 at 2.7-4.3 V, 0.1 C, 0.5 C, 1 C, 3 C, 5 C, 10 C (1 C=180 mAh / g); Figure 7 1 C cycle performance diagram of the positive electrode materials prepared in Examples 1, 2, 3 and Comparative Example 1 within 2.7-4.3 V. DETAILED DESCRIPTION
[0021] As used herein: "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0022] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0023] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0024] In these examples, parts and percentages are by mass unless otherwise indicated.
[0025] "Mass parts" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass parts of component A are a parts and the mass parts of component B are b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass parts of all components is not limited to 100 parts.
[0026] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0027] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0028] This application provides a method for preparing a composite positive electrode material. Figure 1 ,include: S100: introducing a first mixed salt solution containing nickel, cobalt and manganese, a first complexing agent and an alkali solution into the bottom liquid of the reaction kettle to perform a first coprecipitation reaction; S200: After the first coprecipitation reaction, a second mixed salt solution containing lanthanum and zirconium, a second complexing agent and an alkali solution are introduced to perform a second coprecipitation reaction to obtain a precursor slurry; S300: collecting the precipitate from the precursor slurry, washing, and drying to obtain a high-nickel ternary / LLZO composite precursor; S400: Mixing the high nickel ternary / LLZO composite precursor with a lithium source and calcining to obtain a high nickel ternary / LLZO composite positive electrode material.
[0029] The preparation method of the composite positive electrode material provided in the present application simultaneously synthesizes a high-nickel ternary / LLZO composite precursor and a positive electrode material. Compared with the traditional synthesis method of composite positive electrode materials, which requires separately synthesizing high-nickel ternary and LLZO and then compounding the two through other experiments, the method of the present application is similar to the current synthesis route of ternary positive electrode materials, which greatly simplifies the production process of high-nickel ternary / LLZO composite positive electrode materials and reduces production costs.
[0030] The coprecipitation-solid phase method is widely used in the synthesis of ternary cathode materials. The hydroxide precursor is first prepared by coprecipitation, and then the cathode material is synthesized by a high-temperature sintering lithium process. After exploration, the coprecipitation-solid phase method can also be used to synthesize garnet-type solid electrolyte LLZO, but due to the solubility product constant (K sp ) with nickel hydroxide, cobalt hydroxide, manganese hydroxide K sp The gap is more than ten orders of magnitude, resulting in large differences in the co-precipitation reaction conditions of the two, making it difficult to obtain a composite precursor through a one-step co-precipitation. The method of this application is based on co-precipitation-solid phase reaction. By setting different complexing agent concentrations and rotation speeds in the two-stage co-precipitation process, a composite positive electrode material precursor is obtained, and a lithium source is added during the solid phase calcination process, thereby achieving the simultaneous preparation of high-nickel ternary / LLZO composite positive electrode materials, greatly simplifying the process flow of composite positive electrode materials.
[0031] In some embodiments, the total metal ion concentration in the first mixed salt solution in step S100 is 1.4-2.0 mol / L, for example, it can be 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2.0 mol / L or any value between 1.4-2.0 mol / L; the first mixed salt solution can be one or more of sulfate, carbonate, chloride or nitrate.
[0032] In some embodiments, the total metal ion concentration in the second mixed salt solution in step S200 is the same as that in the first mixed salt solution; the total mass of the second mixed salt solution introduced is 0.5%-5% of the mass of the first mixed salt solution, for example, it can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any value between 0.5%-5%; the second mixed salt solution can be one or more of sulfate, carbonate, chloride or nitrate.
[0033] In some embodiments, the first complexing agent in step S100 and the second complexing agent in step S200 are aqueous ammonia solutions, the concentration of the first complexing agent is 0.5-2 mol / L, for example, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2 mol / L or any value between 0.5-2 mol / L, the concentration of the second complexing agent is 0.2-0.8 mol / L, for example, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L or any value between 0.2-0.8 mol / L.
[0034] In some embodiments, the alkali solution in step S100 and step S200 is a NaOH solution, and the concentration of the NaOH solution is 1-4 mol / L, for example, it can be 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L or any value between 1-4 mol / L.
[0035] In some embodiments, the bottom liquid of the reactor in step S100 is an ammonia solution with a concentration of 9-11 g / L.
[0036] In some embodiments, the pH value of the first coprecipitation reaction in step S100 is 9-12, for example, it can be 9, 10, 11, 12 or any value between 9 and 12; the rotation speed of the first coprecipitation reaction is 400-900 rpm, for example, it can be 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, 850 rpm, 900 rpm or any value between 400 and 900 rpm; the temperature of the first coprecipitation reaction is 50-60°C, for example, it can be 50°C, 55°C, 60°C or any value between 50-60°C; the time of the first coprecipitation reaction is 8-12 h, for example, it can be 8 h, 9 h, 10 h, 11 h, 12 h or any value between 8-12 h; the first coprecipitation reaction is carried out under a protective atmosphere.
[0037] In some embodiments, the rotation speed of the second coprecipitation reaction in step S200 is 700-1200 rpm, for example, it can be 700 rpm, 750 rpm, 800 rpm, 850 rpm, 900 rpm, 950 rpm, 1000 rpm, 1050 rpm, 1100 rpm, 1150 rpm, 1200 rpm or any value between 700-1200 rpm; the pH value and reaction temperature of the second coprecipitation reaction are the same as those of the first coprecipitation reaction; the second coprecipitation reaction is carried out under a protective atmosphere.
[0038] In some embodiments, the flow ratio of the mixed salt solution, the complexing agent solution and the alkaline solution in step S100 and step S200 is the same; optionally, the flow ratio of the mixed salt solution, the complexing agent solution and the alkaline solution is 1:0.3:(0.5-2), for example, it can be any ratio between 1:0.3:0.5, 1:0.3:1, 1:0.3:1.5, 1:0.3:2 or 1:0.3:(0.5-2).
[0039] In some embodiments, in step S400, the high nickel ternary / LLZO composite precursor is mixed with a lithium source and calcined, including: The high nickel ternary / LLZO composite precursor is mixed with a lithium source and a flux and calcined.
[0040] Since LLZO usually needs to be sintered at high temperature (above 1000°C) to form a cubic phase with high ionic conductivity, and the lithium source volatilizes severely at this temperature, it will lead to aggravated cation mixing of high-nickel ternary cathode materials, resulting in structural instability and reduced capacity. Therefore, the addition of flux during the solid-phase sintering process effectively reduces the sintering temperature, realizes the simultaneous preparation of high-nickel ternary / LLZO composite cathode materials, greatly simplifies the process flow of composite cathode materials, and makes the LLZO solid electrolyte tightly coated on the surface of high-nickel ternary cathode materials, thereby achieving the purpose of inhibiting the interface side reactions of high-nickel ternary cathode materials and improving battery rate and cycle performance.
[0041] In some embodiments, the flux includes LiF, Li 3 PO 4 、LiBiO 3 One or more of; the amount of flux added is 1%-5% of the molar number of the high nickel ternary / LLZO composite precursor, for example, it can be 1%, 2%, 3%, 4%, 5% or any value between 1% and 5%; the lithium source is one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium sulfate, lithium acetate, lithium phosphate and lithium oxalate.
[0042] In some embodiments, the calcination in step S400 is divided into two stages. The first stage is to heat to 400-600°C and keep warm for 6-10 h, and the second stage is to heat to 700-1000°C and keep warm for 10 h. The heating rate is 1-10°C / min, and the whole calcination process is carried out in an oxygen atmosphere.
[0043] In some embodiments, the chemical formula of the high nickel ternary / LLZO composite precursor is: Ni a Co b Mn 1-a-b (OH) 2 ·cLa 3 Zr 2 (OH) 17 The chemical formula of the high nickel ternary / LLZO composite positive electrode material is: LiNi a Co b Mn 1-a-b O 2 ·cLi 7 La 3 Zr 2 O 12 , where a≥0.6, 0.1≤b≤0.3, 0.5wt% <c<5wt%。
[0044] For example, the operation flow diagram of a specific embodiment of the method for preparing the composite positive electrode material of the present application is as follows: Figure 2 As shown, a mixed sulfate solution A of nickel, cobalt and manganese is coprecipitated with a first complexing agent C and an alkali solution in a first stage, and then a mixed nitrate solution B of lanthanum and zirconium and a second complexing agent D are added to perform a second stage coprecipitation, and then Ni is obtained after aging, washing, filtering and drying. 0.8 Co 0.1 Mn 0.1 (OH) 2 ·La 3 Zr 2 (OH) 17 The composite precursor is finally calcined with a lithium source and a flux to obtain LiNi 0.8 Co 0.1 Mn 0.1 O 2 2% LLZO composite cathode material.
[0045] The present application also provides a composite positive electrode material, which is prepared by the above-mentioned method for preparing the composite positive electrode material.
[0046] The synchronously synthesized high-nickel ternary / LLZO composite positive electrode material provided in the present application has a closer contact and more uniform coating between the LLZO solid electrolyte and the high-nickel ternary material, which improves the lithium ion transmission kinetics while preventing the electrolyte from contacting the highly active Ni 4+Direct contact reduces the production of rock salt phase, and the garnet-type LLZO electrolyte can also enhance the phase change reversibility of high-nickel ternary materials through lithium supplementation strategy, thereby obtaining a composite positive electrode material with high rate performance and high cycle stability.
[0047] The present application also provides a lithium-ion battery, comprising the above-mentioned composite positive electrode material.
[0048] The present application also provides an electrical device, comprising the above-mentioned lithium-ion battery.
[0049] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0050] Example 1 This embodiment provides a method for simultaneously preparing LiNi 0.8 Co 0.1 Mn 0.1 O 2 · A method for preparing a 2 wt.% LLZO composite cathode material, comprising the following steps: Step 1: Prepare a mixed sulfate solution A of nickel, cobalt and manganese, wherein the molar ratio of nickel:cobalt:manganese is 8:1:1, and the total metal ion molar concentration is 1.6 mol / L; prepare a mixed nitrate solution B of lanthanum and zirconium, wherein the molar ratio of lanthanum:zirconium is 3:2, the total metal ion molar concentration is 1.6 mol / L, and the total amount of nitrate solution B introduced is 2% of the mass fraction of sulfate solution A; prepare ammonia complexing agent solution C with a molar concentration of 1 mol / L and ammonia complexing agent solution D with a concentration of 0.6 mol / L; prepare a sodium hydroxide solution with a molar concentration of 2 mol / L as an alkaline solution precipitant; prepare an ammonia solution with a mass concentration of 10 g / L as the bottom liquid of the reactor.
[0051] Step 2: Add 1.6 L of the bottom liquid into the reactor, start the paddle stirring of the reactor, and introduce nitrogen into the reactor at a flow rate of 200 mL / min for more than 20 min to ensure the atmosphere in the reactor and prevent ion oxidation during the subsequent reaction process; pump the mixed sulfate solution A and ammonia complexing agent solution C in step 1 into the reactor at flow rates of 2 mL / min and 0.6 mL / min, respectively, to carry out the first stage of coprecipitation reaction, and maintain the pH value at 11 by the sodium hydroxide solution in the alkali tank, the stirring speed of the reactor is 700 rpm, and the temperature of the reactor system is 55°C. After the coprecipitation reaction is carried out for 10 h, the mixed nitrate solution B is introduced, and the ammonia complexing agent solution C is replaced by the ammonia complexing agent solution D, and the second stage of coprecipitation reaction is carried out, and the rotation speed is increased to 1000 rpm, and the liquid flow rate, pH value and reaction temperature are kept the same as those in the first stage, and the reaction is stopped when the salt solution is consumed.
[0052] Step 3: Reduce the speed to 100 rpm and age for 4 h. Collect the precipitate, wash with deionized water, filter for more than three times to remove sulfate ions and nitrate ions, and then dry in a vacuum oven at 110 °C for 20 h to obtain Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 ·La 3 Zr 2 (OH) 17 Composite precursor.
[0053] Step 4: The composite precursor, lithium source lithium hydroxide and flux LiF were mixed evenly in a molar ratio of 1:1.15:0.02, and calcined in a tube furnace with an oxygen flow rate of 0.6 L / min, first heated to 500°C for pre-calcination for 6 h, then heated to 850°C for calcination for 10 h, with a heating rate of 2°C / min, and cooled to room temperature to obtain LiNi 0.8 Co 0.1 Mn 0.1 O 2 2% LLZO composite cathode material.
[0054] The SEM image of the composite positive electrode material obtained in Example 1 is as follows Figure 3 As shown in Figure 2, it can be seen that the composite cathode material is a secondary particle sphere or spherical structure formed by the accumulation of primary particles, and the secondary particle size is about 10 μm; the XRD diagram is shown in Figure 2 Figure 4 As shown; TEM image Figure 5 As shown in the figure, 0.19 nm is the specific crystal plane spacing of LLZO solid electrolyte, and 0.24 nm is the specific crystal plane spacing of NCM. It can be seen that the LLZO solid electrolyte is tightly coated on the surface of the high nickel ternary positive electrode material.
[0055] This embodiment also provides a lithium ion battery, the preparation method of which includes the following steps: The composite positive electrode material obtained in Example 1, acetylene black and polyvinylidene fluoride were mixed uniformly in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone was added to form a slurry, which was evenly coated on an aluminum foil with a scraper, and vacuum dried at 80°C for 12 h, and then cut into discs with a diameter of 12 mm on a punching machine for use as positive electrode sheets.
[0056] Assemble CR2025 button cell: lithium metal sheet as negative electrode, Celgard2500 as separator, composition is 1 M LiPF 6 A half-cell was assembled with an electrolyte of ethyl methyl carbonate, dimethyl carbonate and ethylene carbonate dissolved in a volume ratio of 1:1:1, and the electrochemical performance was tested.
[0057] Example 2 The difference between Example 2 and Example 1 is that the temperature of the second stage of calcination is adjusted to 1000°C, and other conditions remain unchanged to obtain the composite positive electrode material of Example 2. The XRD pattern is as follows: Figure 4 As shown, the electrochemical performance tests were carried out under the same conditions.
[0058] Example 3 The difference between Example 3 and Example 1 is that the temperature of the second stage of calcination is adjusted to 700° C., and other conditions remain unchanged to obtain the composite positive electrode material of Example 3, and the electrochemical performance test is carried out under the same conditions.
[0059] Example 4 The difference between Example 4 and Example 1 is that in step 1, the concentration of ammonia complexing agent solution C is 0.5 mol / L, the concentration of ammonia complexing agent solution D is 0.2 mol / L, and other conditions remain unchanged to obtain the composite positive electrode material of Example 4, and the electrochemical performance test is carried out under the same conditions.
[0060] Example 5 The difference between Example 5 and Example 1 is that in step 1, the concentration of ammonia complexing agent solution C is 2 mol / L, the concentration of ammonia complexing agent solution D is 0.8 mol / L, and other conditions remain unchanged to obtain the composite positive electrode material of Example 5, and the electrochemical performance test is carried out under the same conditions.
[0061] Example 6 The difference between Example 6 and Example 1 is that the stirring speed of the reactor in the first stage co-precipitation reaction in step 2 is 400 rpm, and the stirring speed of the reactor in the second stage co-precipitation reaction is 700 rpm, and other conditions remain unchanged to obtain the composite positive electrode material of Example 6, and the electrochemical performance test is carried out under the same conditions.
[0062] Example 7 The difference between Example 7 and Example 1 is that the stirring speed of the reactor in the first stage co-precipitation reaction in step 2 is 900 rpm, and the stirring speed of the reactor in the second stage co-precipitation reaction is 1200 rpm, and other conditions remain unchanged to obtain the composite positive electrode material of Example 7, and the electrochemical performance test is carried out under the same conditions.
[0063] Example 8 The difference between Example 8 and Example 1 is that the flux used in step 4 is Li 3 PO 4 , other conditions remain unchanged, to obtain the composite positive electrode material of Example 8, and to carry out electrochemical performance test under the same conditions.
[0064] Example 9 The difference between Example 9 and Example 1 is that no flux is added in step 4, and other conditions remain unchanged to obtain the composite positive electrode material of Example 9, and the electrochemical performance test is carried out under the same conditions.
[0065] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that only the coprecipitation reaction of the first stage high nickel ternary precursor is carried out to synthesize a pure phase high nickel ternary positive electrode material. The XRD diagram is as follows: Figure 4 The specific steps are as follows: Step 1: Prepare a mixed sulfate solution A of nickel, cobalt and manganese, wherein the molar ratio of nickel:cobalt:manganese is 8:1:1 and the total metal molar concentration is 1.6 mol / L; prepare an ammonia complexing agent solution C with a molar concentration of 1 mol / L; prepare a sodium hydroxide solution with a molar concentration of 2 mol / L as an alkaline solution precipitant; prepare an ammonia solution with a concentration of 10 g / L as the bottom liquid of the reactor.
[0066] Step 2: Add the bottom liquid into the reactor, start the paddle stirring of the reactor, and introduce nitrogen into the reactor at a flow rate of 200 mL / min for more than 20 min to ensure the atmosphere in the reactor and prevent ion oxidation during the subsequent reaction process; pump the mixed sulfate solution A and ammonia complexing agent solution C in step 1 into the reactor at flow rates of 2 mL / min and 0.6 mL / min, respectively, for coprecipitation reaction, maintain the pH value at 11 by the sodium hydroxide solution in the alkali tank, stir the reactor at 700 rpm, and the temperature of the reactor system is 55°C. Stop the reaction after the coprecipitation reaction has been carried out for 10 h.
[0067] Step 3: Reduce the speed to 100 rpm and age for 4 h. Collect the precipitate, wash with deionized water, filter for more than three times to remove sulfate ions, and then dry in a vacuum oven at 110 °C for 20 h to obtain Ni 0.8Co 0.1 Mn 0.1 (OH) 2 Precursor.
[0068] Step 4: The precursor, lithium source lithium hydroxide and flux LiF were mixed evenly in a molar ratio of 1:1.15:0.02, and calcined in a tube furnace with an oxygen flow rate of 0.6 L / min. The temperature was first raised to 500°C for pre-calcination for 6 h, and then raised to 850°C for calcination for 10 h at a heating rate of 2°C / min. After cooling to room temperature, LiNi 0.8 Co 0.1 Mn 0.1 O 2 Positive electrode material.
[0069] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that a high-nickel ternary precursor is prepared by coprecipitation reaction, LLZO ceramic powder is prepared by solid phase reaction method, and then the precursor and LLZO powder are co-fired at 1100°C to synthesize a high-nickel ternary / LLZO composite positive electrode material. The specific steps are as follows: Step 1: Prepare a mixed sulfate solution A of nickel, cobalt and manganese, wherein the molar ratio of nickel:cobalt:manganese is 8:1:1 and the total metal molar concentration is 1.6 mol / L; prepare an ammonia complexing agent solution C with a molar concentration of 1 mol / L; prepare a sodium hydroxide solution with a molar concentration of 2 mol / L as an alkaline solution precipitant; prepare an ammonia solution with a concentration of 10 g / L as the bottom liquid of the reactor.
[0070] Step 2: Add the bottom liquid into the reactor, start the paddle stirring of the reactor, and introduce nitrogen into the reactor at a flow rate of 200 mL / min for more than 20 min to ensure the atmosphere in the reactor and prevent ion oxidation during the subsequent reaction process; pump the mixed sulfate solution A and ammonia complexing agent solution C in step 1 into the reactor at flow rates of 2 mL / min and 0.6 mL / min, respectively, for coprecipitation reaction, maintain the pH value at 11 by the sodium hydroxide solution in the alkali tank, stir the reactor at 700 rpm, and the temperature of the reactor system is 55°C. Stop the reaction after the coprecipitation reaction has been carried out for 10 h.
[0071] Step 3: Reduce the speed to 100 rpm and age for 4 h. Collect the precipitate, wash with deionized water, filter for more than three times to remove sulfate ions, and then dry in a vacuum oven at 110 °C for 20 h to obtain Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 Precursor.
[0072] Step 4: Pour lithium hydroxide, lanthanum oxide and zirconium oxide into a zirconium oxide ball mill at a molar ratio of 7:3:2, add an appropriate amount of grinding medium isopropanol, and add yttrium-stabilized zirconium oxide balls at a ball-to-material mass ratio of 10:1, where the ratio of large, medium and small balls is 4:3:3. Then, ball mill for 6 hours at a speed of 400 rpm. Then, load the dried mixed powder into a magnesium oxide crucible, place it in a high-temperature resistance furnace, heat it to 1200°C at a rate of 5°C / min, and keep it warm for 6 hours to obtain LLZO powder.
[0073] Step 5: The aforementioned LLZO powder was ball-milled for the second time. In order to further reduce the powder particle size, the second ball-milling time was increased to 8 h. Then, as in the previous step, the ball-milled slurry was completely dried and then sieved with a 200-mesh screen to obtain fine LLZO powder.
[0074] Step 6: Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 The precursor, lithium hydroxide, flux LiF and LLZO powder were mixed uniformly in a molar ratio of 1:1.15:0.02:0.02, and calcined in a tube furnace with an oxygen flow rate of 0.6 L / min. The temperature was first raised to 500°C for pre-calcination for 6 h, and then raised to 1100°C for calcination for 10 h at a heating rate of 2°C / min. After cooling to room temperature, LiNi 0.8 Co 0.1 Mn 0.1 O 2 2% LLZO composite cathode material.
[0075] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that a high-nickel ternary precursor is prepared by coprecipitation reaction, LLZO ceramic powder is prepared by solid phase reaction method, and then the precursor and LLZO powder are co-fired at 700°C to synthesize a high-nickel ternary / LLZO composite positive electrode material. The specific steps are as follows: Step 1: Prepare a mixed sulfate solution A of nickel, cobalt and manganese, wherein the molar ratio of nickel:cobalt:manganese is 8:1:1 and the total metal molar concentration is 1.6 mol / L; prepare an ammonia complexing agent solution C with a molar concentration of 1 mol / L; prepare a sodium hydroxide solution with a molar concentration of 2 mol / L as an alkaline solution precipitant; prepare an ammonia solution with a concentration of 10 g / L as the bottom liquid of the reactor.
[0076] Step 2: Add the bottom liquid into the reactor, start the paddle stirring of the reactor, and introduce nitrogen into the reactor at a flow rate of 200 mL / min for more than 20 min to ensure the atmosphere in the reactor and prevent ion oxidation during the subsequent reaction process; pump the mixed sulfate solution A and ammonia complexing agent solution C in step 1 into the reactor at flow rates of 2 mL / min and 0.6 mL / min, respectively, for coprecipitation reaction, maintain the pH value at 11 by the sodium hydroxide solution in the alkali tank, stir the reactor at 700 rpm, and the temperature of the reactor system is 55°C. Stop the reaction after the coprecipitation reaction has been carried out for 10 h.
[0077] Step 3: Reduce the speed to 100 rpm and age for 4 h. Collect the precipitate, wash with deionized water, filter for more than three times to remove sulfate ions, and then dry in a vacuum oven at 110 °C for 20 h to obtain Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 Precursor.
[0078] Step 4: Pour lithium hydroxide, lanthanum oxide and zirconium oxide into a zirconium oxide ball mill at a molar ratio of 7:3:2, add an appropriate amount of grinding medium isopropanol, and add yttrium-stabilized zirconium oxide balls at a ball-to-material mass ratio of 10:1, where the ratio of large, medium and small balls is 4:3:3. Then, ball mill for 6 hours at a speed of 400 rpm. Then, load the dried mixed powder into a magnesium oxide crucible, place it in a high-temperature resistance furnace, heat it to 1200°C at a rate of 5°C / min, and keep it warm for 6 hours to obtain LLZO powder.
[0079] Step 5: The aforementioned LLZO powder was ball-milled for the second time. In order to further reduce the powder particle size, the second ball-milling time was increased to 8 h. Then, as in the previous step, the ball-milled slurry was completely dried and then sieved with a 200-mesh screen to obtain fine LLZO powder.
[0080] Step 6: The precursor, lithium hydroxide, flux LiF and LLZO powder were mixed evenly in a molar ratio of 1:1.15:0.02:0.02, and calcined in a tube furnace with an oxygen flow rate of 0.6 L / min. The temperature was first raised to 500°C for pre-calcination for 6 h, and then raised to 700°C for calcination for 10 h at a heating rate of 2°C / min. After cooling to room temperature, LiNi 0.8 Co 0.1 Mn 0.1 O 2 2% LLZO composite cathode material.
[0081] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that a high-nickel ternary precursor is prepared by coprecipitation reaction, LLZO ceramic powder is prepared by solid phase reaction method, and then the precursor and LLZO powder are co-fired at 1200°C to synthesize a high-nickel ternary / LLZO composite positive electrode material. The specific steps are as follows: Step 1: Prepare a mixed sulfate solution A of nickel, cobalt and manganese, wherein the molar ratio of nickel:cobalt:manganese is 8:1:1 and the total metal molar concentration is 1.6 mol / L; prepare an ammonia complexing agent solution C with a molar concentration of 1 mol / L; prepare a sodium hydroxide solution with a molar concentration of 2 mol / L as an alkaline solution precipitant; prepare an ammonia solution with a concentration of 10 g / L as the bottom liquid of the reactor.
[0082] Step 2: Add the bottom liquid into the reactor, start the paddle stirring of the reactor, and introduce nitrogen into the reactor at a flow rate of 200 mL / min for more than 20 min to ensure the atmosphere in the reactor and prevent ion oxidation during the subsequent reaction process; pump the mixed sulfate solution A and ammonia complexing agent solution C in step 1 into the reactor at flow rates of 2 mL / min and 0.6 mL / min, respectively, for coprecipitation reaction, maintain the pH value at 11 by the sodium hydroxide solution in the alkali tank, stir the reactor at 700 rpm, and the temperature of the reactor system is 55°C. Stop the reaction after the coprecipitation reaction has been carried out for 10 h.
[0083] Step 3: Reduce the speed to 100 rpm and age for 4 h. Collect the precipitate, wash with deionized water, filter for more than three times to remove sulfate ions, and then dry in a vacuum oven at 110 °C for 20 h to obtain Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 Precursor.
[0084] Step 4: Pour lithium hydroxide, lanthanum oxide and zirconium oxide into a zirconium oxide ball mill at a molar ratio of 7:3:2, add an appropriate amount of grinding medium isopropanol, and add yttrium-stabilized zirconium oxide balls at a ball-to-material mass ratio of 10:1, where the ratio of large, medium and small balls is 4:3:3. Then, ball mill for 6 hours at a speed of 400 rpm. Then, load the dried mixed powder into a magnesium oxide crucible, place it in a high-temperature resistance furnace, heat it to 1200°C at a rate of 5°C / min, and keep it warm for 6 hours to obtain LLZO powder.
[0085] Step 5: The aforementioned LLZO powder was ball-milled for the second time. In order to further reduce the powder particle size, the second ball-milling time was increased to 8 h. Then, as in the previous step, the ball-milled slurry was completely dried and then sieved with a 200-mesh screen to obtain fine LLZO powder.
[0086] Step 6: The precursor, lithium source lithium hydroxide, flux LiF and LLZO powder were mixed evenly in a molar ratio of 1:1.15:0.02:0.02, and calcined in a tube furnace with an oxygen flow rate of 0.6 L / min. The temperature was first raised to 500°C for pre-calcination for 6 h, and then raised to 1200°C for calcination for 10 h at a heating rate of 2°C / min. After cooling to room temperature, LiNi 0.8 Co 0.1 Mn 0.1 O 2 2% LLZO composite cathode material.
[0087] Figure 6 The rate performance diagram of the positive electrode materials prepared in Examples 1-3 and Comparative Example 1 at 2.7-4.3 V, 0.1 C, 0.5 C, 1 C, 3 C, 5 C, 10 C (1 C=180 mAh / g); Figure 7 The 1 C cycle performance diagram of the positive electrode materials prepared in Examples 1-3 and Comparative Example 1 within 2.7-4.3 V; the rate performance of the composite positive electrode materials of each Example and Comparative Example is shown in Table 1.
[0088] Table 1 Comparison of rate performance of composite positive electrode materials of various embodiments and comparative examples
[0089] According to Table 1, Examples 1 to 8 of the present application simultaneously prepare high-nickel ternary / LLZO composite positive electrode materials by segmented coprecipitation-solid phase method. The process is simple, and the garnet solid electrolyte can be uniformly coated with high-nickel ternary materials, thereby improving the lithium ion transmission kinetics and preventing the electrolyte from reacting with the highly active Ni 4+ Direct contact reduces the production of rock salt phase, and the LLZO electrolyte can also enhance the phase change reversibility of high-nickel ternary materials through lithium replenishment strategy, thereby achieving simultaneous improvement of rate performance and cycle stability.
[0090] In Example 9, no flux is added during the calcination process, and LLZO cannot form a cubic phase with high ionic conductivity. Therefore, the rate performance and cycle stability are not as good as those of Examples 1 to 8, but the cycle performance is slightly higher than that of the pure phase high nickel ternary positive electrode material of Comparative Example 1.
[0091] Comparative Examples 2 to 4 all prepare a high nickel ternary precursor by coprecipitation reaction, and prepare LLZO ceramic powder by solid phase reaction method, and then co-fire the high nickel ternary precursor with LLZO powder to synthesize a high nickel ternary / LLZO composite positive electrode material. It can be seen that the performance of the high nickel ternary / LLZO composite positive electrode material prepared in Comparative Examples 2 to 4 is even worse than that of the pure phase high nickel ternary positive electrode material of Comparative Example 1. This is because LLZO, as an oxide solid electrolyte, has a high ionic conductivity crystal phase (cubic phase) with a very high formation temperature. By simply mixing and co-firing, it is added to the positive electrode material, and a fast ion conductor coating layer cannot be formed on the surface of the positive electrode material crystal in a directional manner, and an impurity crystal phase will also be produced, so the effect of modifying the positive electrode material cannot be achieved. In addition, since the temperature of the mixed co-firing is higher than the solid phase reaction synthesis temperature of the traditional positive electrode material, the crystal structure of the positive electrode material itself will be destroyed to a certain extent, resulting in a decrease in performance. The present application uses a co-precipitation method to prepare the NCM ternary / LLZO composite material, which can directionally form an LLZO layer coating on the surface of the NCM ternary crystal, thereby improving the ion transmission performance between crystals and significantly improving the rate performance.
[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0093] This application provides this technical solution, which promotes the application of high-nickel positive electrode materials in lithium-ion batteries and meets the needs of large-scale commercial promotion. The above is only a preferred embodiment of this application. It should be pointed out that there are many garnet electrolytes and high-nickel ternary components available for selection in this application. They are not listed one by one in the specific embodiments, and all can achieve the purpose of this application.
[0094] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a composite positive electrode material, characterized in that: include: A first mixed salt solution containing nickel, cobalt and manganese, a first complexing agent and an alkali solution are introduced into the bottom liquid of the reaction kettle to perform a first coprecipitation reaction; After the first coprecipitation reaction, a second mixed salt solution containing lanthanum and zirconium, a second complexing agent and an alkali solution are introduced to carry out a second coprecipitation reaction to obtain a precursor slurry; Collecting the precipitate from the precursor slurry, washing, and drying, to obtain a high-nickel ternary / LLZO composite precursor; The high-nickel ternary / LLZO composite precursor is mixed with a lithium source and calcined to obtain a high-nickel ternary / LLZO composite positive electrode material.
2. The method for preparing a composite positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: A. the total metal ion concentration in the first mixed salt solution is 1.4-2.0 mol / L, and the total metal ion concentration in the second mixed salt solution is the same as that in the first mixed salt solution; B. The total mass of the second mixed salt solution introduced is 0.5%-5% of the mass of the first mixed salt solution; C. The first complexing agent and the second complexing agent are aqueous ammonia solutions, the concentration of the first complexing agent is 0.5-2 mol / L, and the concentration of the second complexing agent is 0.2-0.8 mol / L; D. the alkali solution is a NaOH solution, and the concentration of the NaOH solution is 1-4 mol / L; E. The bottom liquid of the reactor is an ammonia solution with a concentration of 9-11 g / L.
3. The method for preparing a composite positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: A. the pH value of the first coprecipitation reaction is 9-12; B. the rotation speed of the first coprecipitation reaction is 400-900 rpm; C. the temperature of the first coprecipitation reaction is 50-60°C; D. the first coprecipitation reaction time is 8-12 h; E. the rotation speed of the second coprecipitation reaction is 700-1200 rpm; F. the pH value and reaction temperature of the second coprecipitation reaction are the same as those of the first coprecipitation reaction; G. both the first coprecipitation reaction and the second coprecipitation reaction are carried out under a protective atmosphere; H. The flow ratio of the mixed salt solution, complexing agent solution and alkaline solution in the two stages is the same; Optionally, the flow ratio of the mixed salt solution, the complexing agent solution and the alkaline solution is 1:0.3:(0.5-2).
4. The method for preparing a composite positive electrode material according to claim 1, characterized in that: The step of mixing the high nickel ternary / LLZO composite precursor with a lithium source and calcining the mixture comprises: The high-nickel ternary / LLZO composite precursor is mixed with a lithium source and a flux, and then calcined.
5. The method for preparing a composite positive electrode material according to claim 4, characterized in that: At least one of the following conditions is met: A. The flux includes one or more of LiF, Li3PO4, and LiBiO3; B. The amount of the flux added is 1%-5% of the molar number of the high nickel ternary / LLZO composite precursor; C. The lithium source is one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium sulfate, lithium acetate, lithium phosphate and lithium oxalate.
6. The method for preparing a composite positive electrode material according to claim 1, characterized in that: The calcination is divided into two stages. In the first stage, the temperature is raised to 400-600°C and kept for 6-10 hours. In the second stage, the temperature is raised to 700-1000°C and kept for 10 hours. The heating rate is 1-10°C / min. The whole calcination process is carried out in an oxygen atmosphere.
7. The method for preparing a composite positive electrode material according to claim 1, characterized in that: The chemical formula of the high nickel ternary / LLZO composite precursor is: Ni a Co b Mn 1-a-b (OH)2·cLa3Zr2(OH) 17 The chemical formula of the high nickel ternary / LLZO composite positive electrode material is: LiNi a Co b Mn 1-a-b O2·cLi7La3Zr2O 12 , where a≥0.6, 0.1≤b≤0.3, 0.5wt% < c< 5wt%.
8. A composite positive electrode material, characterized in that: The composite positive electrode material is prepared by the preparation method of the composite positive electrode material according to any one of claims 1 to 7.
9. A lithium ion battery, characterized in that: Comprising the composite positive electrode material as described in claim 8.
10. An electrical equipment, characterized in that: Includes the lithium ion battery as claimed in claim 9.
Citation Information
Patent Citations
Lithium-ion battery high-nickel ternary positive electrode material with LiYO3 cladded surface and preparation method thereof
CN108232147A
Garnet-type ion conductor-coated high-nickel ternary positive electrode material, preparation method and lithium ion battery obtained by preparation
CN109904427A
Preparation method of lithium lanthanum zirconate coated ternary positive electrode material
CN114068894A
Garnet type structure coated ultrahigh nickel cobalt-free single crystal material and preparation method thereof
CN118983427A
Multi-element positive electrode material and preparation method therefor, and lithium-ion battery
WO2024000155A1
Cited By
LLZO composite solid electrolyte and preparation method and application thereof
CN120987359A